2021
DOI: 10.1007/s40820-021-00599-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Zn Deposition via an Artificial Solid–Electrolyte Interface with Aligned Dipoles for Long Life Zn Anode

Abstract: HIGHLIGHTS• An artificial solid-electrolyte interface composed of a perovskite type material, BaTiO 3 , is introduced to Zn anode surface in aqueous zinc ion batteries.• The BaTiO 3 layer endowing inherent character of the switched polarization can regulate the interfacial electric field at anode/electrolyte interface.• Zn dendrite can be restrained, and Zn metal batteries based on BaTiO 3 layer show stable cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 51 publications
1
101
0
Order By: Relevance
“…Great efforts on solving the severe problems in Zn metal anodes have been proposed by previous researches, most of which involved modification on Zn anode/electrolyte interface and the solvation structure of electrolyte [ 7 9 ]. For instance, strategies like decorating protective layers/solid electrolyte interphase [ 10 19 ], selecting proper separators, constructing three-dimensional alloy structure or regulating crystal orientation could effectively control the Zn ion diffusion and deposition rate [ 18 , 20 27 ], while cut off the pathway of hydrogen evolution reaction (HER), random corrosion and by-products formation to some extent. Besides, another type of important methods focused mainly on designing the composition or state of the electrolyte to change the primary solvation shell constitution or the environment in Zn anode/electrolyte interface, achieving similar functions mentioned before, including introducing different solvent into pure water or small amount of additives [ 28 33 ], constructing highly concentrated “water in salt” structure and utilizing ionic liquid, eutectic liquid, hydrogels or solid-state electrolyte [ 34 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts on solving the severe problems in Zn metal anodes have been proposed by previous researches, most of which involved modification on Zn anode/electrolyte interface and the solvation structure of electrolyte [ 7 9 ]. For instance, strategies like decorating protective layers/solid electrolyte interphase [ 10 19 ], selecting proper separators, constructing three-dimensional alloy structure or regulating crystal orientation could effectively control the Zn ion diffusion and deposition rate [ 18 , 20 27 ], while cut off the pathway of hydrogen evolution reaction (HER), random corrosion and by-products formation to some extent. Besides, another type of important methods focused mainly on designing the composition or state of the electrolyte to change the primary solvation shell constitution or the environment in Zn anode/electrolyte interface, achieving similar functions mentioned before, including introducing different solvent into pure water or small amount of additives [ 28 33 ], constructing highly concentrated “water in salt” structure and utilizing ionic liquid, eutectic liquid, hydrogels or solid-state electrolyte [ 34 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The additional electric field caused by the polarized charge can manipulate the Zn 2+ ion migration. It is recently reported that perovskite-type dielectric material BaTiO 3 (BTO) can be polarized by an external field [ 73 ], and the Ti ions in [TiO 6 ] 2+ deviate from the center of the symmetrical position to form an aligned electric dipole (Fig. 5 a).…”
Section: Design and Optimization Of High-performance Zn Anode In Mild Aqueous Zibsmentioning
confidence: 99%
“…Apart from carbon-based materials, 2D-structured MXene material with metallic conductivity as a modified layer also has a similar effect of homogenizing the local BTO@Zn at 5 mA cm −2 with a capacity of 2.5 mAh cm −2 . The insets reveal the detailed corresponding voltage profiles at various current densities and different cycles [73] electric field (Fig. 6d) [81].…”
mentioning
confidence: 99%
“…The fundamental goal of this strategy is to develop materials that can direct the orderly migration of Zn ions while providing a homogenous electric field at the electrode-electrolyte interface, preventing the formation of Zn dendrites. Recently, it has been demonstrated that an artificial SEI based on BaTiO 3 (BTO) can effectively restrain the Zn dendrite growth ( Figure 17 a,b) [ 125 ]. The polarized BTO layer played a significant role in controlling the orderly migration of Zn ions because of the uniform electric field through it.…”
Section: Common Strategies For Modifying the Surface Of Zn Metal Anodesmentioning
confidence: 99%
“…Cyclic performances of the symmetric cells with Zn and BTO@Zn at ( c ) 1 mA cm −2 (1 mAh cm −2 ), and ( d ) 5 mA cm −2 (2.5 mAh cm −2 ). Reprinted with permission from [ 125 ].…”
Section: Figurementioning
confidence: 99%